2003
DOI: 10.1053/jhep.2003.50202
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Embryonic Stem Cells Into Hepatocytes: Biological Functions and Therapeutic Application

Abstract: Embryonic stem (ES) cells provide a unique source for tissue regeneration. We examined whether mouse ES cells can efficiently differentiate into transplantable hepatocytes. ES cells were implanted into mouse livers 24 hours after carbon tetrachloride intoxication; ES-derived cells with several hepatocyte-cell-markers were generated. They were able to grow in vitro and showed morphology consistent with typical mature hepatocytes and expressed hepatocyte-specific genes. After transplantation into the carbon tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
152
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(155 citation statements)
references
References 34 publications
0
152
1
2
Order By: Relevance
“…To date, numerous studies in rodents have shown that predifferentiated ESC transplantation can reverse acute fulminant hepatic failure 6,50, 51, 52, 53, 54. In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver.…”
Section: Resultsmentioning
confidence: 99%
“…To date, numerous studies in rodents have shown that predifferentiated ESC transplantation can reverse acute fulminant hepatic failure 6,50, 51, 52, 53, 54. In our study, we employed day‐3‐induced DE cells as a source of isolated cells for transplantation into injured liver.…”
Section: Resultsmentioning
confidence: 99%
“…that ES cells can be differentiated into hepatocyte-like cells [1][2][3][4][5][6] . ES cell-derived hepatocytes would be useful as a source of material for cell transplantation, bioartificial liver (BAL) support devices, studies on hepatocyte biology and hepatitis viruses and for drug testing.…”
Section: Protocols Have Been Developed To Differentiate and Enrich Vamentioning
confidence: 99%
“…In vivo differentiation of mouse ES cells has also been accomplished by transplantation into the livers of carbon tetrachloride-treated mice. ES cell-derived hepatocyte precursors have been recovered from the intrahepatic teratomas that form following injury to the liver and ES cell engraftment 1 . These protocols have contributed to our understanding of factors affecting hepatic differentiation by mouse ES cells.…”
Section: Protocols Have Been Developed To Differentiate and Enrich Vamentioning
confidence: 99%
“…Presently remarkable progress has been made in understanding the differentiation of ES cells into neural [Hancock et al, 2000], hematopoietic [Baron, 2001;Perlingeiro et al, 2001;Feng et al, 2005], endothelial , vascular [Sone et al, 2003;Yurugi-Kobayashi et al, 2003;Suzuki et al, 2005], and pancreatic stem/progenitor cells and then various mature cells. However, limited knowledge has been acquired for the differentiation of hepatic progenitor/stem cells, although hepatic differentiation from murine and human ES cells both in vitro and in vivo has been reported in recent studies [Hamazaki et al, 2001;Chinzei et al, 2002;Choi et al, 2002;Ishizaka et al, 2002;Jones et al, 2002;Miyashita et al, 2002;Yamada et al, 2002;Yin et al, 2002;Yamamoto et al, 2003;Kania et al, 2004;Ogawa et al, 2005;Teramoto et al, 2005;Teratani et al, 2005]. These hepatic cells from ES cells expressed some typical markers of mature hepatocytes and showed sufficient functions to rescue experimental liver injury when transplanted in vivo, which raised the hope to generate a transplantable cell source for the treatment of end-stage liver diseases.…”
mentioning
confidence: 99%